Strategies for Preventing Endoscopic Recurrence of Crohn’s Disease 1 Year after Surgery: A Network Meta-Analysis - Jin-shan Feng; Jin-yu Li; Xiu-yan Chen; Zheng Yang; Shang-hai Li (Gastroenterology Research and Practice)
Objective. To assess the benefits of different treatments that aim to prevent the endoscopic recurrence of Crohn’s disease (CD) after ileal resection. Methods. Randomized controlled trials (RCTs) were searched from MEDLINE, Embase, and the Cochrane Central Database. All the included RCTs with an endoscopic recurrence outcome which was defined as Rutgeerts’ score ≥ i2 have a duration of more than 1 year. The quality of the included RCTs was assessed by the Cochrane Risk of Bias Tool. Pairwise treatment effects were estimated through a Bayesian random effects network meta-analysis by using the OpenBUGS 1.4 software and reported as odds ratios (ORs) with a 95% credible interval (CI). Results. Fourteen RCTs (877 participants) were included. Two strategies were superior to placebo for preventing endoscopic recurrence of CD at 1 year after surgery: infliximab (d, −5.475; 95% CI, −10.47 to –1.632) and adalimumab (d, −7.273; 95% CI, −13.84 to −2.585). Nine strategies were not effective: budesnoid, mesalazine (in both high and low dose), azathioprine, Tripterygium wilfordii, mesalazine + infliximab, ornidazole, untreated intervention, and Lactobacillus GG. Conclusions. Except for infliximab and adalimumab, other strategies included in our analysis were not effective for preventing endoscopic recurrence of CD at 1 year after ileal resection.